2020
DOI: 10.3390/ijms21186925
|View full text |Cite
|
Sign up to set email alerts
|

Sensing through Non-Sensing Ocular Ion Channels

Abstract: Ion channels are membrane-spanning integral proteins expressed in multiple organs, including the eye. In the eye, ion channels are involved in various physiological processes, like signal transmission and visual processing. A wide range of mutations have been reported in the corresponding genes and their interacting subunit coding genes, which contribute significantly to an array of blindness, termed ocular channelopathies. These mutations result in either a loss- or gain-of channel functions affecting the str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 295 publications
(382 reference statements)
0
12
0
Order By: Relevance
“…Our discovery that the R919* TRPA1 mutant confers gain-of-function when co-expressed with WT subunits is noteworthy and distinct from the dominant negative or loss-of-function phenotypes observed with most other characterized nonsense channelopathic mutations 45,[77][78][79] . Indeed, a TRPA1 knockout allele that truncates the resulting protein after the S4 transmembrane helix ablates TRPA1 activity in homozygous mice and confers haploinsufficiency in heterozygous animals 26 .…”
Section: Discussionmentioning
confidence: 79%
“…Our discovery that the R919* TRPA1 mutant confers gain-of-function when co-expressed with WT subunits is noteworthy and distinct from the dominant negative or loss-of-function phenotypes observed with most other characterized nonsense channelopathic mutations 45,[77][78][79] . Indeed, a TRPA1 knockout allele that truncates the resulting protein after the S4 transmembrane helix ablates TRPA1 activity in homozygous mice and confers haploinsufficiency in heterozygous animals 26 .…”
Section: Discussionmentioning
confidence: 79%
“…Today is well known how genetic mutations contribute significantly to the wide spectrum of ocular channelopathies [27]. With the advances in sequencing and bioinformatics technologies, screening mutations across these genes, as well as their effect on particular channel protein functions, have become possible [28].…”
Section: Discussionmentioning
confidence: 99%
“…Abnormal physiological functions of the corneal epithelium and nerve endings also contribute to DE pathogenesis (5)(6)(7)(8)(9)(10). These abnormalities, along with the dysfunctional expression and function of ion channels on the surface of the eye, further aggravate subjective symptoms of discomfort from DE (11,12).…”
Section: Introductionmentioning
confidence: 99%
“…Their main physiological function is to maintain the internal and external ecological balance of the cells, sense chemical, temperature, and pressure stimuli, and transmit information (11). At present, many studies have revealed the key role of ion channels present in ocular surface cells in the pathogenesis of DE, and some ion channel activators or inhibitors have shown promise in the targeted treatment of DE (11)(12)(13)(14)(15)(16)(17). This review focused on the research status and progress of studying ion channels related to the ocular surface and DE and summarized the importance of ion channels in the DE to provide insights on DE-targeted drugs.…”
Section: Introductionmentioning
confidence: 99%